Dosis de estiércol de vacuno compostado con bio2 Prohumus y su efecto en las características agronómicas de forraje Gliricidia sepium "mata ratón" en Zungarococha, Perú - 2018 - Tamani Natorce, Gina (2019)
The research on Gliricidia sepium, at the National University of the Peruvian Amazon in the Zugarococha estate, entitled: "DOSAGE OF BOX MANURE COMPOSED WITH BIO2 PROHUMUS AND ITS EFFECT ON THE AGRONOMIC CHARACTERISTICS OF THE FORAGE Gliricidia sepium" IN MATA RATÓNium ZUNGAROCOCHA, PERU - 2018 " Taking as treatments TO (control with 0 tons of cow manure), T1 (5 tons of cow manure / ha), T2 (10 tons of cow manure / ha), T3 (15 tons of cow manure / ha) and T4 (20 tons of cow manure / ha), with a randomized complete block design (DBCA). reaching the following conclusions: that as the dose of Bovine Manure composted with Bio2 Prohumus is increased, the agronomic characteristics of the Gliricidia sepium forage are improved in height, green matter, dry matter, under the agroclimatic conditions that the research was carried out . Regarding the agronomic characteristics, the height of the plant at the 10th. week we can conclude that treatment T4 (20 tons of Bovine Manure Dose composted with Bio2 Prohumus / ha) obtained an average height of 1.39 meters, with an average green matter production of 2.45 Kg / m2 in whole plant, dry matter of 0.49 kg / m2